Patterns of lipid profile abnormalities in hypertensive patients and normotensive subjects: a cross-sectional observational study - Mohan, Chandra; Gururani, Kunal; Rawat, Anurag; Kala, Mansi (International Journal of Research in Medical Sciences, 2021)
Background: It is a well-known fact that hypertension and altered lipid profile or dyslipidaemia are leading risk factors for cardiovascular diseases. The coexistence of these two conditions has remained an interesting matter, among cardiologists and researchers alike. In this study, we analysed the serum lipid patterns of hypertensive patients and normotensive control subjects. Methods: This cross-sectional observational study was conducted in a tertiary healthcare and teaching center of Northwestern India during the period of 2010 and 2011. The study comprised of 100 hypertensive patients and 100 normotensive control subjects. Data were collected regarding demographic details, past medical/drug history and lipid profile including total cholesterol (TC), triglyceride (TG), low density lipoprotein (LDL) and high-density lipoprotein (HDL). Results: A total of 200 subjects with the age above 20 years were enrolled in the study. The mean BMI in hypertensive patients (24.14±2.15 kg/m2) was significantly higher than normotensive subjects (22.60±2.62 kg/m2) (p<0.05). When we compared the mean of TC and TG among the hypertensive patients and normotensive subjects, highly significant differences were obtained (p<0.001). The significant decline in mean HDL level was observed in hypertensive patients than normotensive subjects (40.41±4.57 versus 44.64±5.97, p<0.005). Conclusions: The dyslipidaemia has been more evident among hypertensive patients. Hence, the measurement of blood pressure and lipid profile are of great importance to prevent cardiovascular diseases, stroke and other comorbidities.